Morphological Characterisation and Documentation of Freshwater Macrophytes in Pontian, Johor's Water - SING ONG, YIN; SING TUNG, TENG (UNIMAS Publisher, 2022)
Freshwater macrophytes exist in varied life forms for example, emergent, submerged, floating-leaved and free-floating, and some of them have a heterophylly or multiple forms. The intraspecific variation in terms of morphology is common phenomena in macrophytes population; however, specific studies on morphology of freshwater macrophytes are still insufficient, especially in Pontian, Johor. Hence, this study aimed to characterise the freshwater macrophytes based on morphometrics and descriptive characteristics as well as to document their diversity and population. Thus, the morphometric measurements were done, the descriptive characteristics were documented in scientific photographs, the population of freshwater macrophytes was also estimated by using quadrat estimation technique. Additionally, the morphometrics of some collected samples were compared with the same sample in other studies to show the variation in the range of different measurements, the descriptive characteristics were also described as well as the population estimation assessed by area coverage was analysed in the form of statistical chart. The finding in this study showed variation in morphometric data and no intraspecific variation on phenotype of freshwater macrophytes in Pontian, Johor’s water.